IMPLEMENTASI KEBIJAKAN PEMANFAATAN SUMBER DAYA KEHUTANAN DI KABUPATEN KONAWE SELATAN - Sri Muliati; Jamal Bake; Adrian Tawai (Journal Publicuho, 2018)
The purpose of this study is to analyze the implementation of forestry resource utilization policies, and the factors that influence the successful implementation of forestry resource utilization policies in Konawe Selatan District. This study uses a qualitative research approach to investigate and analyze three pillars of the implementation process, namely the elaboration of policies, organizing the implementing apparatus, and budgeting and spending; and the influence of resource factors, implementing organization characteristics, implementing attitudes, and the conditions of the target group, on the implementation process. Primary and secondary data were collected by interview, observation, and document study methods, then analyzed by interactive analysis procedures which included data reduction, data presentation, and conclusions/verification.The results of the study indicate that the implementation of the policy on the utilization of forestry resources which includes the elaboration of policies, the organizing of the implementing apparatus, and the preparation of budgets and expenditures, has not run effectively. In these three processes there are still gaps so that the achievement of policy objectives seen from the perspective of household welfare, the policy objectives have not been achieved well. The gap in the implementation of forestry resource utilization policies occurs because of the influence of budgetary resource factors that are lower than needed, implementing organizations that do not yet have adequate service standards and human resource competencies, implementation who do not understand the basic tasks and functions of the organization, and target groups who are still depressed by poverty and low education.